2019
DOI: 10.3390/cancers11091301
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with Monoclonal Antibodies in Lung Cancer of Mice: Oxidative Stress and Other Biological Events

Abstract: Background: Lung cancer (LC) is a major leading cause of death worldwide. Immunomodulators that target several immune mechanisms have proven to reduce tumor burden in experimental models through induction of the immune microenvironment. We hypothesized that other biological mechanisms may also favor tumor burden reduction in lung cancer-bearing mice treated with immunomodulators. Methods: Tumor weight, area, T cells and tumor growth (immunohistochemistry), oxidative stress, apoptosis, autophagy, and signaling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Treatment-induced reduction in tumor burden is associated with decreased tumor proliferation but increased oxidative stress, apoptosis, autophagy, and T cell infiltration. The data suggest that treatment with therapeutic antibodies may induce oxidative stress that drives cell cycle arrest and tumor cell death [ 167 ].…”
Section: The Impact Of Cancer Immunotherapies On Oxidative Stress mentioning
confidence: 99%
“…Treatment-induced reduction in tumor burden is associated with decreased tumor proliferation but increased oxidative stress, apoptosis, autophagy, and T cell infiltration. The data suggest that treatment with therapeutic antibodies may induce oxidative stress that drives cell cycle arrest and tumor cell death [ 167 ].…”
Section: The Impact Of Cancer Immunotherapies On Oxidative Stress mentioning
confidence: 99%
“…Another fragment was frozen immediately in liquid nitrogen and preserved at −80 • C for the measurement of protein levels. [37] using conventional immunohistochemistry as previously described [10,38]. Briefly, paraffin-embedded specimens were cut into three-micrometer sections on a microtome.…”
Section: Collection and Preservation Of Samplesmentioning
confidence: 99%
“…At present, the interaction between immune checkpoints and oxidative stress has barely been studied. Tang et al found that treatment with a cocktail of immune checkpoint antibodies increased oxidative stress and T cell in ltration in lung adenocarcinoma [33]. Our data identi ed various immune checkpoints that have a positive correlation with risk scores, among which PD1, PD-L1, and CTLA4 are common targets for ICI therapy in clinical application.…”
Section: Discussionmentioning
confidence: 53%